The Evaluation of the Performance of the Old Lecture Building Using Overall Thermal Transfer Value - Widya Fransiska FA; Isnaini Isnaini (Archvisual: Jurnal Arsitektur dan Perencanaan, 2025)
The old lecture building is one of the campus assets that is still used for lectures. Generally, buildings like this are built with different climate conditions than today. The lecture process requires conducive and comfortable conditions for students and teachers. It is necessary to conduct an evaluation of building performance to assess the building's ability to create comfort for its users. The problem in this study is how the performance of a lecture building that was built more than 50 years ago, whether it can still provide the same comfort as when this building was newly built. This study aims to determine whether the old lecture building is able to create comfort that is in accordance with current lecture activities. To achieve this goal, this study measures the performance of the Lecture Building “I” using the Overall Thermal Transfer Value (OTTV) parameter. This study method is quantitative in the form of calculating the building envelope of Lecture Building “I”, which is the old lecture building of the Faculty of Engineering, Sriwijaya University. The results show that the OTTV value of building I is 38.22 watts/m2. This study concludes that the Lecture Building ”I” has not been able to create comfort for its users. The effect of this is the waste of electrical energy used in air conditioning. The study suggests replacing the opening material with one that reduces heat transmittance to the interior of the building.